Digitalization Of Railway Services As A Factor In Increasing Passenger Comfort: International Experience And Development Vectors In The Republic Of Uzbekistan - Babaeva Sabinabonu Davronbek kizi (Zien Journals, 2025)
This article explores the impact of the digitalization of railway services on enhancing passenger comfort in the Republic of Uzbekistan. Based on an analysis of implemented digital solutions—such as the "Single Window" platform and the mobile application "UzRailway tickets"—the study substantiates their contribution to reducing time and organizational costs, as well as the recovery of passenger traffic following the pandemic. The methodology includes trend and comparative analysis, regulatory content analysis, and statistical visualization. Drawing on international experience (Germany, South Korea, China), the paper identifies strategic directions for the further development of digital services within the transport system. Particular attention is given to the role of digital technologies in increasing the attractiveness of railway transport for foreign tourists. The author offers recommendations for deepening the sector's digital transformation
Keywords: digitalization; railway transport; passenger comfort; Uzbekistan